Modern noise, fluid genres : popular music in Indonesia, 1997-2001 - Wallach, Jeremy (New perspectives in Southeast Asian studies., 2008)
"This book is an ethnographic investigation of Indonesian popular music genres and their producers and listeners during a period of dramatic political and cultural transformation."--Introduction